LRP6 Knockdown Ameliorates Insulin Resistance via Modulation of Autophagy by Regulating GSK3β Signaling in Human LO2 Hepatocytes - Li, Lei; Xue, Jing; Wan, Jipeng; Zhou, Qian; Wang, Shan; Zhou, Yu; Zhao, Heyong; Wang, Xietong (Frontiers in Endocrinology, 2019)
Recent studies suggest that autophagy is highly involved in insulin resistance (IR). Inhibition of the PI3K/AKT/mTOR signaling pathway induces autophagy activation. Additionally, depletion of LRP6 has been shown to increase insulin sensitivity but its mechanism is still not clear. We hypothesized that LRP6 contributes to IR by regulating mTOR mediated autophagy through GSK3β in hepatocytes. LO2 hepatocytes were treated with palmitate (PA) and insulin to induced IR. Levels of LRP6 mRNA and protein expression were measured by real time-PCR and western blot analysis. LRP6 knock down was achieved by adenovirus mediated Si-LRP6 expression and its roles in IR, glucose, GSK3β, mTOR signaling, and autophagy were explored. Finally, GSK3β was overexpressed and its involvement in autophagy and IR was examined. We found that PA treatment led to a reduced glucose uptake and IR in hepatocytes, which was accompanied by an upregulation of LRP6 expression. Knocking down of LRP6 enhanced glucose uptake and insulin sensitivity in PA treated cells, probably through increasing GSK3b activity. Overexpression of GSK3b mimicked LRP6 reduction by enhancing autophagy and ameliorating IR. Our study revealed a significant molecular mechanism connecting LRP6 to insulin sensitivity through GSK3β-mTOR mediated autophagy.